Laboratory Testing for Heparin-Induced Thrombocytopenia and Vaccine-Induced Immune Thrombotic Thrombocytopenia Antibodies: A Narrative Review - Warkentin, Theodore E.; Greinacher, Andreas (Seminars in Thrombosis and Hemostasis, 2022)
Heparin-induced thrombocytopenia (HIT) and vaccine-induced immune thrombotic thrombocytopenia (VITT) are highly prothrombotic (thrombosis frequency ≥50%). Both are caused by platelet-activating anti-platelet factor 4 (PF4) antibodies, forming PF4/IgG-containing immune complexes that engage platelet FcγIIa receptors, producing strong platelet activation. In HIT, heparin crosslinks several PF4 molecules, whereas in VITT, anti-PF4 antibodies alone crosslink PF4. Sufficient levels of circulating anti-PF4 antibodies are needed to create the pathogenic immune complexes on platelet surfaces; this explains why certain serum (plasma)-based assays are highly sensitive for detecting HIT/VITT antibodies. Accordingly, HIT and VITT are “clinical-pathological” disorders, that is, positive testing for such antibodies—together with a compatible clinical picture—is integral for diagnosis. Heparin (low concentrations) enhances HIT antibody-induced platelet activation, but platelet activation by VITT sera is usually inhibited by heparin. For both HIT and VITT, high sensitivity (>99% and >95%, respectively) characterizes PF4-dependent enzyme immunoassays (EIAs) and PF4-enhanced platelet activation assays; in contrast, certain rapid immunoassays have high sensitivity for HIT (>90-97%) but poor sensitivity (<25%) for VITT. HIT and VITT antibodies are directed at distinct sites on PF4: solid-phase EIAs and platelet activation assays are indifferent to these distinct antigen targets, but rapid immunoassays are not. We discuss a conceptual model where PF4 is viewed as a “globe,” with the heparin-binding site the “equator”; in this model, HIT antibodies are primarily directed at antigen site(s) at the north and south “poles” of PF4 (formed when PF4 binds to heparin), whereas VITT antibodies recognize sites on the equator.
Keywords: enzyme immunoassay; heparin-induced thrombocytopenia; platelet factor 4; platelet-activating antibodies; vaccine-induced immune thrombotic thrombocytopenia